MENCEGAH PERNIKAHAN DINI DEMI TERWUJUDNYA GENERASI UNGGUL DI SEKOLAH MENENGAH KEJURUAN (SMK) MIFTAHUL ULUM KABUPATEN SEMARANG - Mukharom Mukharom; Amri Panahatan Sihotang (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
Marriage is a marriage ceremony binding ceremony that is celebrated or carried out by two people to formalize the marriage bond in religious law, state law, and customary law. Early marriage is a great institution to tie two teenage opposite sex people into one family bond. Several factors cause first marriage, namely personal factors and family factors. So far, there are still many communities, including students who do not know the impact of early marriage. Therefore it is necessary to do Community Service in the form of students' understanding of Semarang Regency Miftahul Ulum Vocational School about Prevention of Early Marriage to Realize Superior Generation. This service is doing by lecturing, and direct question and answer and evaluation after the activity carried out. This service carried out in a team. The implementation was carried out by the University of Semarang Faculty of Law Lecturer, who was competent in mastering the material regarding the prevention of early marriage to realize superior generations. Community service was held with a concentration on the prevention of first marriage for the sake of the realization of excellent productions.